(untitled) (Zamonaviy dunyoda ijtimoiy fanlar, 2026)
This article examines the “ultima ratio” principle in criminal law — the idea that criminal legislation should be applied only as a last resort. This principle defines the limits of the application of criminal law, aiming to prevent excessive criminalization and punishment. The article analyzes the historical formation of the principle, its application in modern legal systems, and its theoretical approach. It also discusses the principle's role in law, its relationship with the principles of subsidiarity and proportionality. The article highlights the significance of the ultima ratio principle in ensuring the legitimacy and effectiveness of criminal law through the views of foreign scholars.